The Priority Of Islamic Inheritance Distribution To Heirs In Order To Maintain Problems In The Family - Maswandi Maswandi (International Asia Of Law and Money Laundering, 2023)
This article aims to describe the implementation of Islamic inheritance law and compare the application of Islamic inheritance law with customary inheritance law in the distribution of inheritance among muslim communities . The method used in analyzing these problems in a normative manner, namely describing the phenomenon of the implementation of the Islamic inheritance division which is currently still ruled out even though it is a priority for umatislam . The next stage is compare the implementation of the division of inheritance by using Islamic law or customary law. The findings stated that some of the residents in the three regions still maintain customary law in the division of inheritance, namely the transfer of inheritance occurs when the heir is still alive (Grant) and the same amount between male and female heirs or at will of the heir however, there are among the residents of the region who still maintain Islamic law in the division of inheritance, namely by dividing it after the Heir Dies.